Indigenous firsts : a history of Native American achievements and events - Dennis, Yvonne Wakim; Hirschfelder, Arlene B.; Molin, Paulette Fairbanks (Visible Ink Press, 2023)
"Indigenous Firsts: A History of Native American Achievement and Events recognizes and honors 2,000 barrier-breaking trailblazers and history-making events in multiple fields-arts, entertainment, business, sovereignty, education, government, religion, science, sports, music, and more"--